2013
DOI: 10.1002/joc.3725
|View full text |Cite
|
Sign up to set email alerts
|

Probability analysis of monthly rainfall on seasonal monsoon in Pakistan

Abstract: Pakistan experiences the southwest monsoon normally from July to September every year. In this paper, we analyse the effect of monthly rainfall for the months of July, August and September on overall seasonal monsoon for the period of 1960–2006 across 37 different meteorological stations of Pakistan. The statistical results are based on the notion of conditional probability. We find conditional probabilities of seasonal monsoon to be in excess, deficient and normal when the monthly rainfall of July, August and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The climate ranges from arid subtropical with an average temperature of 17.5–30.4°C and rainfall 150–200 mm in southern Punjab to semi‐arid tropical with an average temperature of 10.5–24.4 °C and rainfall 315–600 mm in central Punjab. The majority of the rain occurs during the monsoon season (July–September) in Punjab (Ahmad et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The climate ranges from arid subtropical with an average temperature of 17.5–30.4°C and rainfall 150–200 mm in southern Punjab to semi‐arid tropical with an average temperature of 10.5–24.4 °C and rainfall 315–600 mm in central Punjab. The majority of the rain occurs during the monsoon season (July–September) in Punjab (Ahmad et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Krishnamurti 1985;Webster and Lukas 1992;Lau et al 2000;Ding and Chan 2005;Bhat et al 2002;Johnson et al 2004;Webster 2005;Singh and Ranade 2010;Saeed et al 2011;Imran et al 2014;Rasul and Chaudhry 2010). The summer monsoon rainfall over the subcontinent has great social, agricultural, and economic value (Ahmad et al 2014). The summer monsoon contributes 65-75% of the total annual rainfall in Pakistan (Ahmad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The summer monsoon rainfall over the subcontinent has great social, agricultural, and economic value (Ahmad et al 2014). The summer monsoon contributes 65-75% of the total annual rainfall in Pakistan (Ahmad et al 2014). The summer monsoon rainfall in Pakistan provides water replenishment which allows the water requirements to be fulfilled during the transition period until the onset of winter rainfall (Imran et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of their suitability to modelling of extreme value, these probability distributions have numerous applications for environmental data (e.g., An and Pandey, 2005;Furrer and Katz, 2008;Chikobvu and Sigauke, 2013;Jonathan and Ewans, 2013;Diriba et al, 2015;Ahmad et al, 2016). Several studies based on frequentist approaches have been conducted for finding the best fit distribution and modelling the AMDR data in Pakistan by Rasul et al (2004), Haroon and Rasul (2009), Rasul et al (2009) and Ahmad et al (2014Ahmad et al ( , 2016. Ahmad et al (2016) suggested that the (GEV) and (GP) are the most suitable distribution for the AMDR series in the different regions of Pakistan.…”
Section: Introductionmentioning
confidence: 99%